Impact of Communication, Motivation, Work Discipline, and Environment on Employee Performance: A Study at a Manufacturing Firm: Pengaruh Komunikasi, Motivasi, Disiplin Kerja, dan Lingkungan Kerja terhadap Kinerja Karyawan: Sebuah Studi di Perusahaan Manufaktur - Rona Tanjung; Rahman Hasibuan; Balqis Allyah Agus; Dini Anggraini; Widodo Ismanto (Universitas Muhammadiyah Sidoarjo, 2023)
This study examines the influence of communication, motivation, work discipline, and work environment on employee performance within a manufacturing context. With a sample size of 90 employees, a structured questionnaire was employed for data collection, followed by validity and reliability assessments, classic assumption tests, multiple linear regression analysis, and hypothesis testing using SPSS V25. Findings revealed that communication style significantly impacted employee performance, while motivation, work discipline, and work environment did not exhibit significant effects. However, when considered collectively, the variables of communication, motivation, work discipline, and work environment exhibited a significant influence on employee performance, offering valuable insights for optimizing performance enhancement strategies in similar organizational settings. Highlight: Holistic Examination: Investigating the impact of communication, motivation, work discipline, and work environment on employee performance in a manufacturing context. Methodological Rigor: Employing a structured questionnaire and advanced statistical analyses, including validity and reliability assessments, classic assumption tests, multiple linear regression, and hypothesis testing. Integrated Insights: Revealing a significant influence of communication style on employee performance, while motivation, work discipline, and work environment individually did not exhibit significant effects. However, their combined effect underscores their collective importance for optimizing performance enhancement strategies in similar organizational settings. Keyword: Communication, Motivation, Work Discipline, Work Environment, Employee Performance